Belangrike ontwikkelings in gesondheidsdienslewering in die republiek van suid-afrika gedurende die sewentigerjare - Odelia Muller (AOSIS, 1981)
A number of major developments have brought about important changes in the delivery and co-ordination of health services in South Africa. Some of these developments are: - the hospital-centric community-directed health services which were developed in the national states; - the changes to programme-budgeting which highlighted priority areas; - the Health Act 63 o f 1977 which provides for a formal structure for co-ordination of health services and the development of national health policy; - rationalisation in the civil service by which one Department of Health, Welfare and Pensions was created; - the Health Services Facilities Plan announced by the Minister of Health in 1980. This plan will greatly enhance the development of comprehensive health services for the South African community. The plan describes six levels according to which health services will be developed: providing for basic health needs; health education; primary health care (including self-care, community responsibility, community nursing and community health centres); the community hospital; the regional hospital; the academic hospital.